A Unifying Framework for Agency in Hypermedia Environments - Charpenay, Victor; Käfer, Tobias; Harth, Andreas (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2022)
One of the emerging trends in engineering multi-agent systems (MASs) is to use the Web as an environment. On the Web, hypermedia is the guiding principle of agent perception and action. Web standards allows agents to have a single uniform interface to their environment, be it real or simulated. Most recent proposals for hypermedia MASs tend, however, to introduce a coupling between agents or between agents and their environment. This paper introduces a framework based on Semantic Web technologies to formalize interactions between agents and a hypermedia environment. Semantic Web technologies and, more specifically Web ontologies, guarantee interoperability on the Web and maximize uncoupling between components. We show how existing ontologies can be used to make existing MAS prototypes fit our framework. Our framework formalizes the guiding principle of agent-environment interactions in hypermedia, state transfer, with respect to a reference formalism originally introduced by Genesereth and Nilsson. We also show the equivalence between the two in the paper, under certain conditions.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Hypermedia; Linked Data; Multi-agent system; Semantic Web